Mediating Religious Cultures in Early Modern Europe - Milner, Matthew; Kirby, Torrance (Newcastle upon Tyne : Cambridge Scholars Publishing, 2013)
In recent years, writing on early-modern culture has turned from examining the upheavals of the Reformation as the ruptured birth of early modernity out of the late medieval towards a striking emphasis on processes of continuity, transition, and adaptation. No longer is the 'religious' seen as institutional or doctrinaire, but rather as a cultural and social phenomenon that exceeds the rigid parameters of modern definition. Recent analyses of early-modern cultures offer nuanced accounts that ...
Contributors; acknowledgements; abbreviations and acronyms; illustrations; part i; chapter one; chapter two; chapter three; chapter four; part ii; chapter five; chapter six; chapter seven; part iii; chapter eight; chapter nine; part iv; chapter ten; chapter eleven; chapter twelve; bibliography
Description based upon print version of record.
Keywords: Europe -- Religion -- Congresses; Europe -- Religion -- History; Religious tolerance -- Europe; Europe -- Religion -- Congresses; Europe -- Religion -- History; RELIGION / Comparative Religion; RELIGION / Essays; RELIGION / Reference; Electronic books